Penerapan Metode Customer Satisfaction Index dalam Sistem Pelaporan Masalah untuk Mengungkap Emosi Pelanggan - Hidayat, Achmad Lutfi; Cahyana, Rinda; Fatimah, Dini Destiani Siti (Jurnal Algoritma, 2023)
Reporting or complaints are communications made to convey conditions that can be used for consideration in making decisions about services. Drinking Water Services (PAM) is managed by the Mekarwangi Village Owned Enterprise. When a problem occurs with the service, the customer must make a report to the officer by coming directly to the BUMDes office, which sometimes records the complaint being lost so it is not conveyed to the technician and results in the problem report not being handled immediately. . Based on these problems, the aim of this research is to build a Village PAM problem reporting system so that customers can report directly their complaints, so that the Rational Unified Process (RUP) methodology is the choice which has Inception, Elaboration and Construction stages, while for modeling Unified Modeling is implemented Language (UML) and black box testing as system testing. The results of this research were successful in developing a web-based system by applying the Customer Satisfaction Index method to the problem reporting system to reveal customer expressions. Knowing the customer's condition can help PAM Desa to immediately handle problems, so that service quality can be maintained and the service provided meets customer expectations. The problem reporting service system can run well based on the results of the functional suitability calculation which obtains a percentage value of 100%, or in the sense that it meets the criteria.